Предмет: Алгебра,
автор: regina12398
(49^x) - (9*7^x-0,5) +2 =0
Ответы
Автор ответа:
0
49^x-9*7^(x-0,5)+2=0
7^2x-9*7^x/√7+2=0
7^x=v ⇒
v²-9v/√7+2=0 I√7
√7*v²-9v+2*√7=0 D=25 √D=5
v₁=2/√7 v₂=√7
7^x=2/7^0,5 7^(x-0,5)=2 log₇7^(x-0,5)=log₇2 x-0,5=log₇2 x₁=0,5+log₇2
7^x=7^0,5 x₂=0,5.
7^2x-9*7^x/√7+2=0
7^x=v ⇒
v²-9v/√7+2=0 I√7
√7*v²-9v+2*√7=0 D=25 √D=5
v₁=2/√7 v₂=√7
7^x=2/7^0,5 7^(x-0,5)=2 log₇7^(x-0,5)=log₇2 x-0,5=log₇2 x₁=0,5+log₇2
7^x=7^0,5 x₂=0,5.
Похожие вопросы
Предмет: Математика,
автор: Nurtimur777
Предмет: История,
автор: taranlilia1
Предмет: Информатика,
автор: annatarskaya06
Предмет: Обществознание,
автор: ageev1
Предмет: Литература,
автор: vfhbzmail008